The treatise of Lorenzo Valla on the Donation of Constantine - Valla, Lorenzo, 1407-1457; Coleman, Christopher Bush, 1875-1944 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Treatise of Lorenzo Valla on the Donation of Constantine" by Lorenzo Valla is a critical historical treatise written in the early 15th century. The primary topic of this work revolves around the analysis and refutation of the purportedly authentic legal document known as the Donation of Constantine, which claimed to grant extensive powers and territories to the Roman Pontificate. Through his examination, Valla asserts the document is a forgery, challenging the foundations of papal authority and its implications for secular power in medieval Europe. At the start of the text, Valla sets his stage for a bold critique of the Donation, addressing the potential backlash he faces for contesting a well-accepted narrative that legitimized papal supremacy. He emphasizes the historical significance of the Donation and how its acceptance shaped the relationship between the church and secular rulers. Valla's opening arguments highlight the absurdities and inconsistencies within the Donation's claims, including questions about the motivations of Constantine and the supposed acknowledgment by the papacy. He establishes his intent to promote a rigorous method of historical criticism, aiming to dismantle long-held misconceptions while laying groundwork for modern scholarly inquiry. (This is an automatically generated summary.)
Release date is 2023-02-20
deaurider and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Constitutum Constantini; Popes -- Temporal power -- Early works to 1800; Church and state -- Holy Roman Empire